Antioxidant Activity Of The Peel Citrus sinensis. L On The Histological Features Of Second Degree Burned Mus musculus - Samsudin, Rinza Rahmawati; Arimurti, Anindita Riesti Retno; Puspitasari, Renny Novi (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2024)
Burns are damage to the tissue that does not only occur on the surface of the skin, but can occur under the skin. Globally, burns are the fourth most common type of injury, after traffic accidents, falls and physical abuse. The cost of treating burns is relatively expensive according to the area of the burn, the larger the area of the burn, the higher the cost of treatment. Research for the treatment of burns using herbal ingredients has begun to be carried out by many researchers. One of the typical Indonesian herbal plant ingredients is the Pacitan orange (Citrus sinensis) L Osbeck. This type of research is an experimental research with the aim of looking at the formation of epithelial cells, fibroblasts, and collagen which are formed after being given Pacitan orange peel extract (Citrus sinensis) treatment. The sample of this study used 20 white rats which were divided into 4 groups, namely Group 1 (K1) the burn group without treatment, Group 2 (K2) the burn rats with bioplacenton treatment, Group 3 (K3) the burn rats with NaCl treatment 0.9%, Group 4 (K4) burnt rats treated with extra 100% Pacitan orange peel. From the research results obtained, it can be concluded that the administration of Pacitan Orange Peel extract is proven to accelerate the healing process of second degree burns on the skin of white rats viewed microscopically, namely from increased collagen production, epithelial thickness, and fibroblasts.Keywords: Pacitan orange peel extract, Burns, Mus musculus, histopathology